NtWRKY33 involved in senescence-induced nornicotine synthesis by activating NtE4 in tobacco - Zhang, Xingzi; Wang, Jin; Wang, Yaqi; Jiang, Caihong; Yang, Aiguo; Li, Fengxia (Plant physiology and biochemistry, 2025)
Nornicotine is an undesirable alkaloid in tobacco due to its unpleasant taste and potential toxicity. The accumulation of nornicotine in tobacco leaves is related to the development of the leaves, with very low amounts present in green leaves and a dramatic increase after senescence. While it is known that the NtE4 is a key enzyme involved in nicotine to nornicotine conversion in tobacco leaves, the specific genes regulating the expression of NtE4 during leaf senescence remain unclear. In this study, we identified a WRKY transcription factor, NtWRKY33, as being involved in nornicotine accumulation during senescence. NtWRKY33 is a nuclear protein and its expression is induced by senescence. Knocking out NtWRKY33 significantly decreased nornicotine levels in senescent leaves, whereas overexpressing NtWRKY33 significantly increased nornicotine accumulation. RT-qPCR analysis demonstrated that NtWRKY33 positively regulates the expression of NtE4 without significantly affecting other key enzyme genes involved in nornicotine biosynthesis. Yeast one-hybrid (Y1H) and dual-luciferase analysis (DLA) revealed that NtWRKY33 directly promotes NtE4 expression by binding to its promoter. Therefore, NtWRKY33 is a transcription factor involved in senescence-induced nornicotine accumulation. This study provides novel insights into the molecular mechanisms by which senescence induces nornicotine formation and identifies a new target for regulating nornicotine levels. •NtWRKY33 is induced by senescence.•NtWRKY33 positively regulates nornicotine biosynthesis.•NtWRKY33 directly promotes NtE4 expression by binding to its promoter.